A study of the corporate governance of thrifts - Cook, Douglas O.; Hogan, Arthur; Kieschnick, Robert (Journal of Banking & Finance, 2004)
We study corporate governance within the thrift industry during a period of industry distress and legally mandated regulatory vigilance. We find evidence consistent with the Office of Thrift Supervision displacing the disciplinary role of takeovers in the market for thrift control. Poorer prior thrift performance is associated with a greater likelihood of censure while better prior performance is associated with a greater likelihood of acquisition. For thrifts that are not censured or acquired, there is no relationship between current performance and managerial turnover. Replacement due to retirement rather than board discipline explains most of these turnovers. This result is consistent with the notion that regulation may deter board disciplinary behavior, also suggested by Kole and Lehr [Journal of Financial Economics 52 (1999) 79].